2011
DOI: 10.1016/j.bmcl.2010.10.121
|View full text |Cite
|
Sign up to set email alerts
|

Click chemistry inspired one-pot synthesis of 1,4-disubstituted 1,2,3-triazoles and their Src kinase inhibitory activity

Abstract: Two classes of 1,4-disubstituted 1,2,3-triazoles were synthesized using one-pot reaction of α-tosyloxy ketones/α-halo ketones, sodium azide, and terminal alkynes in the presence of aq PEG (1:1, v/v) using the click chemistry approach and evaluated for Src kinase inhibitory activity. Structure-activity relationship analysis demonstrated that insertion of C(6)H(5)- and 4-CH(3)C(6)H(4)- at position 4 for both classes and less bulkier aromatic group at position 1 in class 1 contribute critically to the modest Src … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 34 publications
0
31
3
Order By: Relevance
“…21 Previously, it was shown that "click" synthesis of 1,4-disubstituted 1,2,3-triazoles proceeded in good yields using CuSO 4 + NaAsc in PEG 400/water under mild conditions for a short time, due to very efficient activation by PEG 400. [22][23][24][25] However this effect is not observed in the present study, because similar yields were obtained when compared between A and B under different catalysts loading. It appears that the concentration of PEG played a key role in the previous studies (PEG 400/water = 1:1, v:v).…”
Section: Introductioncontrasting
confidence: 81%
See 1 more Smart Citation
“…21 Previously, it was shown that "click" synthesis of 1,4-disubstituted 1,2,3-triazoles proceeded in good yields using CuSO 4 + NaAsc in PEG 400/water under mild conditions for a short time, due to very efficient activation by PEG 400. [22][23][24][25] However this effect is not observed in the present study, because similar yields were obtained when compared between A and B under different catalysts loading. It appears that the concentration of PEG played a key role in the previous studies (PEG 400/water = 1:1, v:v).…”
Section: Introductioncontrasting
confidence: 81%
“…It appears that the concentration of PEG played a key role in the previous studies (PEG 400/water = 1:1, v:v). [22][23][24][25] Here the present PEG concentration is too low to provide such an effect, and therefore the PEG ligand does not lead to a good yield. When the monofunctional 1,2,3-triazole terminated with PEG 2000 (PEG-mono-trz-Cu I , 1 equiv., C), 26 was introduced the yields increased, especially that under low catalyst amounts (i.e.…”
Section: Introductionmentioning
confidence: 91%
“…KP-A021, 3-(4-fluorophenyl)-2-{4-[1-(3-morpholino-3-oxopropyl)-1H-1,2,3-triazol-4yl]phenyl}acrylo-nitrile ( Figure 1a) is the compound of in-house chemical library, which consists of diverse heterocycles, and was synthesized as described previously. 12,17 Osteoclast differentiation Osteoclast differentiation was induced following a previously described method. 18 Briefly, murine bone marrow cells isolated from the tibiae and femora of ICR mice (Dae Han Bio Link.…”
Section: Materials and Antibodiesmentioning
confidence: 99%
“…[42] Considering the biological potential of such conjugates, the same group has reported a novel consecutive three-component synthesis of furan-based hydroxytriazole derivatives 15 starting from d-glucal (14) (Scheme 10). The resulting triazole derivatives 20 have been screened for their function as Src kinase inhibitory [49] and potential antifungal drugs. [44,45] a-Halo and a-tosyloxy carbonyl compounds are particularly reactive in nucleophilic substitutions and, therefore, they are well-suited for the in situ generation of a-azido carbonyl derivatives.…”
Section: Azide Formation Via Nucleophilic Aliphatic Substitutionmentioning
confidence: 99%